Rancang Bangun Sistem Penggajian Karyawan Berbasis Web Dengan Metode Rapid Application Development: (Studi Kasus: PT. Gelumbang Agro Sentosa) - yudiastuti, Helda; Irwansyah; Dinny Komalasari; Sandi Maulidika (Jurnal Ilmiah Matrik, 2025)
This research aims to design and develop a web-based payroll system for PT. Gelumbang Agro Sentosa to enhance efficiency and accuracy in managing payroll data. The previous manual payroll process often led to calculation errors, delays, and difficulties in data storage and tracking. To address these issues, the Rapid Application Development (RAD) method was applied, allowing for fast software development through iterative cycles of design, construction, and testing. The system was developed using the CodeIgniter framework, which supports efficient and modular application development. The result of this study is a web-based payroll application capable of managing employee data, automatically calculating salaries based on components such as basic salary, allowances, and deductions, and generating digital payslips. Based on testing and evaluation, the developed system effectively minimizes calculation errors, accelerates the payroll process, and facilitates documentation and reporting. Thus, the system contributes positively to improving the administrative performance of the human resources department at PT. Gelumbang Agro Sentosa.